Analisis Perbedaan Tingkat Online Engagement Antara Tipe Dan Waktu Post Pada Akun Instagram Klien Kenalkan.Co Di Samarinda - Thalita Rizky Amalia (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Companies can use social media, Instagram to interact and share information. This study aims to determine how post type and time post have effect on online engagement and as a recommendation for managing posts to increase online engagement. This research uses post data from December 2018 to November 2019 on Kenalkan.co client's. The hypothesis was tested using comparison test. The result is type post has significant effect on likes and does’nt have a significant effect on comments. Month post has a significant influence on online engagement. Days post does’nt have a significant effect on online engagement.